The news writing formula a manual for reporters and editors - Santos, Vergel O. (Espana, Manila, Philippines Universty of Santo Tomas Publishing House, 2020)
Thirty years after its first publication, this new edition of The News Writing Formula clarifies some points in the old book, and also adds updated tips on news editing as well as suggestions on grammar and usage as they might apply to the English used in the news. --Back cover.
Chapter 1: Hounding the news -- Chapter 2: Deadline writing -- Chapter 3: Copyediting -- Chapter 4: Watchlist.
Keywords: Journalism -- Authorship; Feature writing